Developing a coach education course: A bottom-up approach - Jacobs, F.; Knoppers, A.; Diekstra, R.; Sklad, M. (International Sport Coaching Journal, 2015)
A frequent critique of coach education courses is that they are designed by scholars with little input from coaches about what they think they need. The purpose of this paper is to describe the design and content of a coach education course that was grounded in stakeholder needs. Dutch amateur football coaches felt ill-equipped to handle conflicts and confrontational behaviors by players and/ or parents. Therefore a coach education course was created to help coaches develop tools they could use to improve their interpersonal skills. The tools were drawn from the teaching strategies of Forgatch and DeGarmo (1999) and Rational-Emotive Education (REE) (Knaus, 1974). Keywords: coach education, interpersonal skills, soccer coaches